Evaluasi Penggunaan Antibiotik Pada Pasien Dewasa Dengan Penyakit Gonore Di RS "X" Periode Januari 2013-Juli 2016 - Dewi, Rafika Surya, Hidayah Karuniawati,M., Sc., Apt (2016)
Gonorrhea is a sexually transmitted disease caused by the bacterium Neisseria gonorrhoeae can be treated using antibiotics. However, the use of antibiotics freely and irrational can cause antibiotic resistance so as to increase morbidity and mortality of a disease. One effort that can be done to prevent the occurrence of antibiotic resistance is by evaluating the rationality of its use. This study aims to determine the rationality of antibiotic use are reviewed through the proper indications, the right patient, the right medication and the right dosage. This research is non-experimental research conducted ervational data medical records of adult patients with gonorrhea outpatient Dr. Moewardi Surakarta Hospital period January 2013 to July 2016. The sample used is purposive sampling and analyzed by descriptive non analytic to describe the actual antibiotic use in adult patients with gonorrhea outpatient Dr. Moewardi Surakarta Hospital period January 2013-July 2016 and compared to a standard Manual Handling Sexually Transmitted Infections 2011 MoH RI. The results of the 88 cases studied, the antibiotics used in cases of gonorrhea are cefixime (58%), azithromycin (46.6%), xycycline (36.4%), ofloxacin (21.6%), levofloxacin (6.8 %), ciprofloxacin (4.6%), metronidazole and sefditoren (2.3%), ceftriaxone and chloramphenicol (1.1%), there were 88 cases (100%) the proper indications and appropriate patients, 47 cases (53.4 %) the right medicine, 41 cases (46.6%) the right dose, and which fulfills the rationality of 46.6%.